Neuritin: a multifaceted neuroprotective factor with emerging applications for neurodegeneration - Mongan, Kai L.; Sharma, Tasneem P. (Frontiers in Neuroscience, 2025)
Neuritin is a conserved, activity-regulated gene encoding a glycosylphosphatidylinositol-anchored protein, crucial for neural development, synaptic plasticity, and neuroprotection. Identified via activity-dependent gene screening in the rat hippocampus, neuritin promotes neurite outgrowth, dendritic arborization, and synaptic maturation with neural activity. In this review, we summarize recent findings regarding neuritin’s signaling pathways, neuroprotective, neuroregenerative, and neuromodulatory properties, with a focus on its therapeutic potential to counter neurodegeneration in various conditions such as glaucoma, Alzheimer’s disease, stroke, diabetic neuropathy, and neuropsychiatric disorders. Additionally, recent studies reveal roles in immunoregulation, angiogenesis, and cancer biology, highlighting neuritin as a versatile signaling molecule with broad therapeutic implications.